2017
DOI: 10.1371/journal.pone.0180630
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal microbiota in infants and changes during viral upper respiratory tract infection and acute otitis media

Abstract: BackgroundInterferences between pathogenic bacteria and specific commensals are known. We determined the interactions between nasopharyngeal microbial pathogens and commensals during viral upper respiratory tract infection (URI) and acute otitis media (AOM) in infants.MethodsWe analyzed 971 specimens collected monthly and during URI and AOM episodes from 139 infants. The 16S rRNA V4 gene regions were sequenced on the Illumina MiSeq platform.ResultsAmong the high abundant genus-level nasopharyngeal microbiota w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 34 publications
6
102
1
1
Order By: Relevance
“…In recent years, we and others have demonstrated that the upper airway bacterial microbiome plays an important role in the pathogenesis and pulmonary sequelae of viral ARIs. [9][10][11][12][13][14][15][16][17] For example, several studies in murine models have shown that priming of the nasal mucosa with certain taxa (such as Lactobacillus species) increases the resistance and beneficially modulates the immune response of mice against RSV, influenza, and pneumonia virus. 9,10 In a recent study of young children with RSV ARI, higher nasopharyngeal abundances of Haemophilus influenzae and Streptococcus were associated with a more proinflammatory immune response and a higher risk of hospitalization.…”
Section: Abbreviations Used Ari: Acute Respiratory Infection Inspirementioning
confidence: 99%
“…In recent years, we and others have demonstrated that the upper airway bacterial microbiome plays an important role in the pathogenesis and pulmonary sequelae of viral ARIs. [9][10][11][12][13][14][15][16][17] For example, several studies in murine models have shown that priming of the nasal mucosa with certain taxa (such as Lactobacillus species) increases the resistance and beneficially modulates the immune response of mice against RSV, influenza, and pneumonia virus. 9,10 In a recent study of young children with RSV ARI, higher nasopharyngeal abundances of Haemophilus influenzae and Streptococcus were associated with a more proinflammatory immune response and a higher risk of hospitalization.…”
Section: Abbreviations Used Ari: Acute Respiratory Infection Inspirementioning
confidence: 99%
“…Although obtaining a nasopharyngeal (NP) swab is minimally invasive, performance of multiple tests usually requires obtaining multiple specimens. Although some investigators have reported using nasal samples for multiple tests, (1)(2)(3)(4)(5) we are not aware of any studies that have used a single NP swab to evaluate viral, bacterial and host parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The Qiagen software identified all phyla whereas the alternative software could not assign 15% of bacterial DNA and this may be explained by the higher stringency set for the Qiagen software. There is not standard for stringency but these results suggest that although the higher stringency reduces the number of reads included in the analysis, the results are highly comparable to other methods and 17 and (in some situations) CF 18 . In the research setting, sampling from the upper airways has been validated as a surrogate for lower airway sampling 19,20 .…”
Section: Discussionmentioning
confidence: 86%